Pengembangan Media Monopoli untuk meningkatkan Pemahaman siswa materi bersatu dalam keberagaman pada mata pelajaran PPKN di kelas 3 Sekolah Dasar - Fitri Rahmawati; Okpatrioka Okpatrioka (International Forum of Researchers and Lecturers, 2023)
The purpose of this research is to determine the effect of using monopoly media to increase students' understanding of material unity in diversity in the environment of grade 3 students at Sugutamu Elementary School. The type of research used is quantitative with research and development methods. The research design used was Pretest-Posttest. Therefore, the population used was all 3rd grade students at SDN development and pilot schools. This can be seen based on the average score obtained by students in the experimental class which was better than the control class, 78.39>71.61. Based on the results of the t-test using SPSS, the significance value (2-tailed) is 0.000<0.05, so HO is rejected and Ha is accepted. Therefore, it can be concluded that there is an influence of using monopoly media to increase students' understanding of the material unity in diversity in class 3 students' subjects, so that monopoly media can be used by teachers to increase understanding of the concept of unity in diversity.